2012
DOI: 10.1177/0093854811428565
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorder and Offending in Prison

Abstract: This research uses specific diagnoses and symptoms of mental disorder (MDO) to predict whether inmates offend in prison. Social psychological theories of aggression are used to make predictions about what types of MDO affect whether inmates commit violent and nonviolent infractions. The analysis was based on a survey of a nationally representative sample of more than 16,000 inmates from state and federal facilities. The evidence suggests that psychosis and major depression have strong effects on infractions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 53 publications
4
64
0
Order By: Relevance
“…First, existing studies (e.g., Trestman et al, 2007) note that many offenders with SMI are not identified as mentally ill upon entry into the system. Given that mental health problems in offenders are linked to greater likelihood of violent crimes, longer sentences, rule violations, and physical assaults in the corrections environment (Felson, Silver & Remster, 2012;James & Glaze, 2006), greater knowledge and understanding of these offenders and their needs is critical for the success of behavioral health treatment programs, jail management, and correctional staff safety. Understanding female offenders' pathways to offending helps elucidate the complexity of their experiences and identify key factors and intervening variables that may ameliorate or exacerbate risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, existing studies (e.g., Trestman et al, 2007) note that many offenders with SMI are not identified as mentally ill upon entry into the system. Given that mental health problems in offenders are linked to greater likelihood of violent crimes, longer sentences, rule violations, and physical assaults in the corrections environment (Felson, Silver & Remster, 2012;James & Glaze, 2006), greater knowledge and understanding of these offenders and their needs is critical for the success of behavioral health treatment programs, jail management, and correctional staff safety. Understanding female offenders' pathways to offending helps elucidate the complexity of their experiences and identify key factors and intervening variables that may ameliorate or exacerbate risk.…”
Section: Discussionmentioning
confidence: 99%
“…It also appears that having specific disorders may increase risk. In a survey of 16,000 male and female inmates conducted by Furthermore, Felson, Silver & Remster (2012), these authors reported that individuals with major depressive disorder and psychotic disorders were more likely than individuals with other disorders or individuals without mental illness to engage in both violent and nonviolent infractions while incarcerated. Thus, assessing for presence of specific disorders has implications both in regards to meeting treatment needs of incarcerated individuals as well as addressing the safety of corrections staff and other offenders.…”
Section: Research On Mental Health Of Female Offendersmentioning
confidence: 99%
“…Another study found that mentally ill inmates were charged with rule violations at a higher rate than nonmentally ill inmates, including 58% compared to 43% in state prisons, 40% compared to 28% in federal prisons, and 19% compared to 9% in jails ( James & Glaze, 2006). Rule violations, both violent and nonviolent, are more common in offenders with depression and psychosis, as well as in those who experience hopelessness, paranoia, and hallucinations (Felson, Silver, & Remster, 2012).…”
Section: Causesmentioning
confidence: 99%
“…Psychosis and depression are also associated with nonaggressive offences, suggesting that these precipitate many kinds of misconduct [17]. Psychosis and depression are also associated with nonaggressive offences, suggesting that these precipitate many kinds of misconduct [17].…”
Section: Prevalence Of Mental Disorders In Prisonmentioning
confidence: 99%